Grassland ecophysiology and grazing ecology - Lemaire, G.; Carvalho, P. C. de F.; Carvalho, P. C. de F.; Hodgson, J.; Hodgson, J.; Lemaire, G.; Moraes, A. de; Moraes, A. de; Nabinger, C.; Nabinger, C. (Wallingford :CABI Publishing, 2000)
This book consists of edited and revised versions of the 20 invited papers presented at an International Symposium on Grassland Ecophysiology and Grazing Ecology held at Curitiba, Parana, Brazil on 24-26 August 1999. The papers are on the sustainability of grazing systems (1); environmental constraints and plant responses to defoliation (4); morphogenesis of pasture species and adaptation to defoliation (4); plant-animal interactions (4); sustainable grazing management of natural pastures (4); and problems of animal production related to pastures in subtropical and temperate regions of South America (3). All papers are abstracted separately.
Keywords: FF007 - Forage and Fodder Crops, (New March 2000); FF030 - Plant Morphology and Structure; FF060 - Plant Physiology and Biochemistry; FF150 - Plant Cropping Systems; LL300 - Animal Behaviour; PP350 - Grasslands and Rangelands; South America